2015
DOI: 10.4103/0974-1208.153119
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation in female cancer patients: An overview

Abstract: Fertility preservation is becoming increasingly important to improve the quality of life in cancer survivors. Despite guidelines suggesting that discussion of fertility preservation should be done prior to starting cancer therapies, there is a lack of implementation in this area. A number of techniques are available for fertility preservation, and they can be used individually or together in the same patient to maximize efficiency. Oocyte and embryo cryopreservation are now established techniques but have thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 59 publications
0
86
0
1
Order By: Relevance
“…The use of chemoprotective agents for gonadal tissues has received considerable attention in recent years. This is due to the simplicity of this approach, the lower toxicity induced by these natural compounds (Mahajan, ) and also due to the limitations of the current methods for fertility preservation. Several studies have shown that natural products obtained from different plants can mitigate or prevent the negative impacts caused by chemotherapy on fertility and this approach can be considered safe (Ilbey et al., ; Kalthur et al., ; Nayak et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of chemoprotective agents for gonadal tissues has received considerable attention in recent years. This is due to the simplicity of this approach, the lower toxicity induced by these natural compounds (Mahajan, ) and also due to the limitations of the current methods for fertility preservation. Several studies have shown that natural products obtained from different plants can mitigate or prevent the negative impacts caused by chemotherapy on fertility and this approach can be considered safe (Ilbey et al., ; Kalthur et al., ; Nayak et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…54 In vitro maturation of oocytes derived from preantral follicles which are spared in POI can be used as one of the treatment options. 1 Ovarian Preservation 56,57 To avoid follicular damage in young women requiring chemotherapy or radiotherapy for cancer, the following measures can be taken:…”
Section: Management Of Infertilitymentioning
confidence: 99%
“…Embryo cryopreservation is not suitable for pre-pubertal patients in whom ovaries are still pre-pubertal. 10 Embryo cryopreservation provides a good success rate depending on the number and quality of embryos stored. A retrospective analysis done by Cardoza et al in 2015 11 noted a 37% pregnancy rate and 30% cumulative live birth rate in cancer patients who underwent Frozen Embryo Transfer (FET) which was comparable to 43% pregnancy rate and 32% cumulative pregnancy rates (p=0.49 and p =0.85 respectively) in women undergoing IVF for tubal infertility.…”
Section: Testicular Tissue/sperm Preservation In Pre-pubertal Boysmentioning
confidence: 99%